Social Work and the Development of Community-Based Social Services - Blinkevičiūtė, Vilija (Socialinė teorija, empirija, politika ir praktika, 2001)
The present text is the opening and welcome speech to the 4 international conference “Social work and the development of community services”, which was in 2001, Vilnius, November 23-24. The speaker was Vilija Blinkevčiūtė - the minister of Social security and work ministry of Lithuania Republic. The minister welcomed the participants of conference and presented the goals of the Eleventh Government of the Republic of Lithuania to develop and enhance the social assistance system.